The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1540-8191.2007.00542.x
|View full text |Cite
|
Sign up to set email alerts
|

Life-Threatening Pulmonary Embolism Associated with a Thrombus Straddling a Patent Foramen Ovale: Report of a Case

Abstract: The risk of systemic embolization during thrombolytic or heparin treatment for biatrial thrombus makes most authors recommend surgical or interventional thrombectomy and PFO closure. Given the limited number of cases, there is no evidence that any of the treatment strategies provide a better survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…Intracardiac thrombus being more fragile usually presents with evidence of pulmonary, systemic embolism, and coronary embolism. [ 7 ] It should be removed by wide base resection as soon as possible because of higher frequency of embolization. [ 8 ] Echocardiography gives significant number of clues such as the polypoid or smooth surface myxoma, the site of origin, satellite focus, and diastolic blockage of mitral or tricuspid inflow which almost support provisional diagnosis of cardiac myxoma.…”
Section: Discussionmentioning
confidence: 99%
“…Intracardiac thrombus being more fragile usually presents with evidence of pulmonary, systemic embolism, and coronary embolism. [ 7 ] It should be removed by wide base resection as soon as possible because of higher frequency of embolization. [ 8 ] Echocardiography gives significant number of clues such as the polypoid or smooth surface myxoma, the site of origin, satellite focus, and diastolic blockage of mitral or tricuspid inflow which almost support provisional diagnosis of cardiac myxoma.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first reported case to our knowledge of simultaneous aortic root replacement and pulmonary embolectomy for massive PE. The closure of a patent foramen ovale and removal of intracardiac thrombi along with pulmonary embolectomy have commonly been described [1], but it is unusual to perform pulmonary embolectomy simultaneously with another major cardiac procedure. Performing pulmonary embolectomy at the same time as coronary artery bypass grafting and atrial myxoma resection has been reported on infrequent occasions [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike osteoarthritis, SJI affects younger patients and is often the result of the illicit use of intravenous drugs, immune compromise, trauma, central venous catheterization, or seeding from concomitant infection. There are case reports of SJI occurring in healthy individuals [1]. Pseudomonas sp.…”
mentioning
confidence: 99%
“…Options include surgical thrombectomy with PFO closure, thrombolysis and systemic heparin therapy [5]. Secondary prophylaxis against paradoxical embolism is usually achieved with anticoagulant therapy, although there is great interest in a potential role for percutaneous PFO closure devices.…”
Section: Paradoxical Embolism Is Rarely Proven As the Passage Of Embmentioning
confidence: 99%